'Speaking about the unspeakable': Clinical psychologists views on the role of the profession regarding 'forced care' of older adults without capacity. (February 2019) - Watts, Sarah J.; Jackman, Louisa; Howarth, Alan
'Forced care' describes the provision of personal care to an individual who does not have the capacity to make a decision about that care and resists receiving that care. This study explored the views of clinical psychologists on supporting staff involved with forced care and considered the following question: Do clinical psychologists feel that they have a role in guiding decisions around forced care, and if so, what? Interview data were gathered from five clinical psychologists experienced in the field of Older Adult psychology in the UK. This study concludes that the environment in which psychologists work influences the psychologist's beliefs about whether psychologists should be involved with making recommendations about forced care, and how they should be involved.